Underwater low-velocity gas flow measurement based on passive acoustics with stable volume resolution. (19th October 2020) - Zhang, Yu; Feng, Zhu; Rui, Xiaobo; Yue, Guixuan; Huang, Xinjing
Abstract: Underwater gas escape is widespread in the marine and industrial fields and the low-velocity gas caused by trace gas escape is difficult to be detected or measured. An underwater low-velocity gas flow measurement method based on passive acoustics with stable volume resolution is proposed in this paper. The elastic wave signal generated by the underwater gas is acquired by a hydrophone and filtered by the wavelet packet filtering method. The flow rate can be cumulatively estimated by the relationship between the bubble and the spectrum characteristics. The volume resolution of the bubble is stable, which is achieved by adjusting the signal frequency resolution. This method is adaptive to the processing of bubbles in different volumes. The stable volume resolution is helpful to reduce the random error for the cumulative continuous bubble volume estimation. Underwater gas leakage experimental platforms were established under laboratory conditions and lake conditions. The results show that the method has high accuracy and stability. For a single bubble and low-velocity flow conditions under laboratory conditions, the minimum error is 0.3% and the maximum error is 3.9% between 5 and 25 ml min −1 . For the low-velocity flow under lake conditions, the minimum error is 0.8% and the maximum error is 8% between 10 and 60 ml min −1 .